2021
DOI: 10.1002/cam4.4372
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns and survival in metastatic castration‐sensitive prostate cancer in the US Veterans Health Administration

Abstract: Background Limited real‐world data exist on treatment patterns and outcomes in patients with metastatic castration‐sensitive prostate cancer (mCSPC). Methods A retrospective cohort study was conducted, using the Veterans Health Administration claims database (April 2013–March 2018). Among 369,734 prostate cancer patients, we selected all men who developed metastases within 90 days before or after medical/surgical castration and who received androgen deprivation therapy (ADT). Patients were categorized into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Previous studies analyzing real-world data have described treatment patterns for mHSPC. Two recently published studies by Ryan et al 35 and Freedland et al 36 showed an increase in AAP usage since 2017, which agrees with the general trend found in our study. However, we found that overall usage of AAP was slightly lower in our cohort.…”
Section: Without Comorbiditiessupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies analyzing real-world data have described treatment patterns for mHSPC. Two recently published studies by Ryan et al 35 and Freedland et al 36 showed an increase in AAP usage since 2017, which agrees with the general trend found in our study. However, we found that overall usage of AAP was slightly lower in our cohort.…”
Section: Without Comorbiditiessupporting
confidence: 93%
“…There are 2 possible explanations for this discrepancy. First, Ryan et al 35 reported their uptake rate as the proportion of men receiving AAP in their sample stratified by the year of first metastasis diagnosis, and Freedland et al 36 reported the proportion of AAP use among all men receiving therapy in the year they evaluated. Moreover, both studies focused on individuals with insurance coverage, which differs from our cohort that includes both insured and uninsured men.…”
Section: Without Comorbiditiesmentioning
confidence: 99%
“…First, nearly all studies to date were conducted in patient populations that did not receive ARPI in the mCSPC setting (i.e., they received ADT monotherapy or in combination with taxanes). Potent ARPI are increasingly used in patients with mCSPC, 9 and new studies will need to assess the prognostic implication of AR amplification detection in a post‐ARPI‐treated mCRPC population. Second, detection of AR amplification in liquid biopsy requires that a sample contains relatively high levels of ctDNA or CTCs.…”
Section: Ar Amplificationmentioning
confidence: 99%
“…Second, emerging radionuclide therapies (e.g., 177 Lutetium [Lu]‐prostate‐specific membrane antigen [PSMA]) 4,5 or genomic biomarker‐directed therapies (e.g., poly [ADP‐ribose] polymerase [PARP] inhibitors) 6,7 are further crowding an already complex treatment landscape. Third, although recent phase III clinical trial data supports ARPI use early in the disease course and in combination with taxanes, 8 real‐world evidence suggests that the majority of men with metastatic castration‐sensitive prostate cancer (mCSPC) continue to be treated with androgen deprivation therapy (ADT) alone 9 . Together, these challenges mean that treatment patterns frequently differ geographically and between similarly presenting patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation